Price discount, influencer and impulsive buying: When emotions overpower logic on social media - Mertaningrum, Ni Luh Putu Erma; Giantari, I Gusti Ayu Ketut; Ekawati, Ni Wayan; Setiawan, Putu Yudi (Edelweiss Applied Science and Technology, 2025)
This study examines the effect of price discounts and influencer credibility on consumer impulsive buying behavior, with positive emotion mediation and self-control moderation. Combining the Stimulus-Organism-Response (S-O-R) theory, emotion regulation theory, and the elaboration likelihood model (ELM), this study offers a comprehensive theoretical approach to understanding consumer purchasing decisions in the digital era. The researchers collected data through an online survey of 190 respondents who used social media and followed fashion product influencer accounts. They analyzed the data using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) approach. The results revealed that price discounts and influencer credibility significantly influenced positive emotions and impulsive buying behavior. Positive emotions also played a significant mediating role in the relationship between influencer credibility and impulsive buying. Furthermore, the researchers found that self-control moderated the relationship between emotional involvement and impulsive buying, indicating that individuals with low self-regulation are more likely to engage in impulsive purchases.